2004
DOI: 10.1161/01.atv.0000117181.68309.10
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression and Involvement of Cyclooxygenase-2 in Human Megakaryocytopoiesis

Abstract: Objective-Cyclooxygenase-1 (COX-1), but not COX-2, is expressed in human platelets, and thromboxane A 2 (TXA 2 ) produced via COX-1 induces platelet aggregation. The objectives of this study were to investigate the expression of COX-1 and COX-2 during platelet differentiation and to determine whether these enzymes are involved in the differentiation. Methods and Results-CD34ϩ progenitor cells isolated from human cord blood were cultured with thrombopoietin and c-kit ligand. The cells differentiated into megaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
(37 reference statements)
0
26
0
2
Order By: Relevance
“…In light of previous evidence of COX-2 expression in mature megakaryocytes from normal [24][25][26][27][28][29] and ET 30 bone marrow specimens, and of in vitro data showing that platelet COX-2 might contribute to TXA 2 biosynthesis in hematopoietic hyperregenerative conditions (eg, recovery after bone marrow transplantation), 24 we sought to explore the contribution of platelet COX-2 to TXA 2 biosynthesis in ET. Etoricoxib, a highly selective COX-2 inhibitor, 42 was used as a pharmacologic tool to test this hypothesis in vivo, along with experiments adding a selective COX-2 inhibitor, NS-398, in vitro to blood samples from aspirin-treated ET patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of previous evidence of COX-2 expression in mature megakaryocytes from normal [24][25][26][27][28][29] and ET 30 bone marrow specimens, and of in vitro data showing that platelet COX-2 might contribute to TXA 2 biosynthesis in hematopoietic hyperregenerative conditions (eg, recovery after bone marrow transplantation), 24 we sought to explore the contribution of platelet COX-2 to TXA 2 biosynthesis in ET. Etoricoxib, a highly selective COX-2 inhibitor, 42 was used as a pharmacologic tool to test this hypothesis in vivo, along with experiments adding a selective COX-2 inhibitor, NS-398, in vitro to blood samples from aspirin-treated ET patients.…”
Section: Discussionmentioning
confidence: 99%
“…22 Aspirin achieves its antithrombotic effect by permanently and selectively inactivating platelet cyclooxygenase 1 (COX-1), thus blocking TXA 2 biosynthesis. 23 It has been shown that COX-2 is up-regulated during megakaryopoiesis, 24 is expressed by normal megakaryocytes and circulating young platelets, [24][25][26][27][28][29] and it is overexpressed in bone marrow megakaryocytes of ET patients. 30 Under conditions of physiologic thrombopoiesis, platelet COX-2 does not appear to contribute to TXA 2 production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TPR activation is also known to Four milligrams of protein of isolated extranuclear (E) and nuclear (N) fractions from rat OPCs/OLGs was incubated with the TPR-immunoaffinity matrix. After washing, the bound proteins were eluted, subjected to SDS-PAGE, and probed using antibodies against TPR and various G␣ subunits: G q , G 13 (29,34,47), and is thought to be involved in apoptosis (11,49). As is the case with other GPCRs, TPRs have been shown to activate multiple G proteins, in particular G q and G 13 ( 10, 23, 35, 45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increases in MCP-1 secreted by the platelets could increase the immune response in the circulation. COX2 levels were shown to be up-regulated during megakaryocyte maturation [48][49] and have an effect on this process. 49 Increases in both TLR2 and NFB1 further enhance the megakaryocyte TLR2 cell-surface recognition of PAMPs and increase the number of signaling proteins to respond to any activation of this receptor.…”
Section: Effects Of Tlr2 On Megakaryocytic Cell Function 5971mentioning
confidence: 99%